2019
DOI: 10.1590/fst.41617
|View full text |Cite
|
Sign up to set email alerts
|

Co-crystallization of paprika oleoresin and storage stability study

Abstract: Paprika oleoresin was co-crystallized to formulate a natural and hydrophilic dye for use in food applications. The color stabilities of the co-crystallized and free oleoresins were evaluated at different temperatures (25 and 35 °C, 70% RH) and light exposures (light 70 watts and dark, 25 °C, 70% RH). Co-crystallization from supersaturated sucrose syrup (S = 1.32) was found to be optimum for the formation of sugar agglomerates in a few minutes, with the paprika oleoresin entrapped inside. With time, decreases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Deladino et al (2007) analysed co-crystallized systems with yerba mate extract and different salts and obtained bulk density values between 0.65 and 0.72 g/cm 3 , similar to CP40 bulk density value. Federzoni et al (2019) also found a similar result (0.789 g/cm 3 ) for paprika oleoresin co-crystallized powders.…”
Section: Particle and Flow Properties Of Cp Powderssupporting
confidence: 71%
See 3 more Smart Citations
“…Deladino et al (2007) analysed co-crystallized systems with yerba mate extract and different salts and obtained bulk density values between 0.65 and 0.72 g/cm 3 , similar to CP40 bulk density value. Federzoni et al (2019) also found a similar result (0.789 g/cm 3 ) for paprika oleoresin co-crystallized powders.…”
Section: Particle and Flow Properties Of Cp Powderssupporting
confidence: 71%
“…In addition, propolis itself could contribute to microbiological safety of the powder due to its antimicrobial (Fangio et al, 2019;Kalogeropoulos et al, 2009) and antifungal (Agüero et al, 2014) properties. Other authors (Federzoni et al, 2019;Nik et al, 2019;Sarabandi et al, 2018) reported similar values of water amounts in co-crystallized products.…”
Section: Physicochemical Characteristics Of the Propolis Co-crystalli...supporting
confidence: 52%
See 2 more Smart Citations
“…Several co‐crystallization processes have been reported in the literature. Studies have been carried out on the encapsulation of fruit juice (Andrade Pizarro, Blanquicett Gónzalez, & Rangel terraza, R., 2017; Astolfi‐Filho et al., 2005), essential oils and plant extracts (Beristain, Vazquez, Garcia, & &Vermnon‐Carter, E.J., 1996), yerba mate (Ilex paraguariensis) and mineral salts (Lorena, Anbinder, Navarro, & Martino, 2007), zinc sulfate (Lopez‐Cordoba et al, 2016) and co‐crystallization of cardamomand paprika oleoresin (Federzoni, Alvim, Fadini, Silva, & Queiroz, 2019; Sardar & Singhal, 2013), all using sucrose as a crystallization agent.…”
Section: Introductionmentioning
confidence: 99%